2010
DOI: 10.1039/c0cc00770f
|View full text |Cite
|
Sign up to set email alerts
|

Host–guest chemistry with bi- and tetra-nuclear macrocyclic metallasupramolecules

Abstract: Among the reported two-dimension macrocycles, bi- and tetra-nuclear macrocyclic metallasupramolecules are designed to have novel specific cavities with different shapes and dimensions, and demonstrate good selectivity and binding for planar aromatic guests and small organic molecules. This feature article focus on the progress in the development of host-guest behavior of bi- and tetra-nuclear macrocyclic metallasupramolecules. Examples in which X-ray structural determination is essential for establishing the r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
34
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 137 publications
(34 citation statements)
references
References 64 publications
0
34
0
Order By: Relevance
“…We also found that these di‐NHCs with extended polyaromatic linkers imparted unique catalytic properties that we ascribed to supramolecular interactions between aromatic substrates and the polyaromatic cores of the ligands . Because rectangle‐like species have demonstrated unique binding abilities and selectivities for planar aromatic guests, we thought that our nanosized Janus‐di‐NHCs may introduce interesting applications for host‐guest chemistry, and for this reason we became interested in developing a series of molecular rectangles for the selective recognition of organic molecules. In particular, we predicted that the structural features of the pyrene‐linked di‐NHC ligand C (Scheme ), could be used for the preparation of molecular rectangles with the potential to recognize polycyclic aromatic hydrocarbons (PAHs) by means of π–π‐stacking interactions.…”
Section: Introductionmentioning
confidence: 95%
“…We also found that these di‐NHCs with extended polyaromatic linkers imparted unique catalytic properties that we ascribed to supramolecular interactions between aromatic substrates and the polyaromatic cores of the ligands . Because rectangle‐like species have demonstrated unique binding abilities and selectivities for planar aromatic guests, we thought that our nanosized Janus‐di‐NHCs may introduce interesting applications for host‐guest chemistry, and for this reason we became interested in developing a series of molecular rectangles for the selective recognition of organic molecules. In particular, we predicted that the structural features of the pyrene‐linked di‐NHC ligand C (Scheme ), could be used for the preparation of molecular rectangles with the potential to recognize polycyclic aromatic hydrocarbons (PAHs) by means of π–π‐stacking interactions.…”
Section: Introductionmentioning
confidence: 95%
“…Several general synthetic approaches to the preparation of discrete metallacycles have emerged, which include directional bonding [46,47], symmetry interactions [48,49], and weak-link approaches [50]. Many impressive examples of metallosupramolecular materials can be found in studies reported by Lehn [1,49,70], Sauvage [51], Stang [46,47], Fujita [26][27][28][29][30][31], Mirkin [50], Hupp [52][53][54][55], Lees [56][57][58][59], Lu [60,61], Jin [62,63], and others [64][65][66][67]. Lehn et al demonstrated the spontaneous self-assembly of dinuclear helicates from bipyridine and copper (I) [70].…”
Section: Introductionmentioning
confidence: 98%
“…The biological, photophysical and redox properties of metallosupramolecular architectures have all been examined. However, it is the interesting host–guest chemistry of these metallosupramolecular systems which shows the most potential. Architectures with hollow cavities, such as capsules and cages, are of particular interest due to the tunable nature of the internal cavities.…”
Section: Introductionmentioning
confidence: 99%
“…Strategies for the synthesis of two-and three-dimensional metallosupramolecular architectures [1] are now well understood and ar ange of applications for theses ystems are beginningt o emerge.T he biological, [2] photophysical [3] and redox [4] properties of metallosupramolecular architectures have all been examined.H owever,i ti st he interesting host-guest chemistry [5] of these metallosupramolecular systemsw hich shows the most potential. Architectures with hollow cavities, such as capsules and cages, are of particulari nterestd ue to the tunable nature of the internal cavities.…”
Section: Introductionmentioning
confidence: 99%